RAGAM FENOTIPE IKAN TENGADAK Barbonymus schwanenfeldii (Bleeker 1854) HASIL SILANG LUAR - Firda Amalia Sukma; Muhammad Fariduddin Ath-Thar; Odang Carman; Deni Radona (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Outbreed may increase genetic diversity and produce better offspring. Meanwhile, genetic diversity can be inferred from phenotypes variability. This study aimed to analyze the diversity of phenotypic characters from four populations of tinfoil barb outbreed, namely Java (J), Kalimantan (K), ♀ Java × ♂ Kalimantan (JK) and ♀ Kalimantan × ♂ Java (KJ).Analysis of the phenotypic diversity was calculated based on truss morphometric on 30 individuals sampled from each populations. The growth and survival rate were measured for 40 days reared. The study was conducted experimentally using a completely randomized design (CDR) with three replications.Rearing four population of tinfoil barb, beginning with acclimatization for two weeks and was continued reared using 12 aquaria40x30x30 cm3. Each aquaria was filled with 10 individual seeds/20 L-1 water with the size of 18,66±1,34 g weight and 8,28±0,34 cm of length. Feeding was done three times a day on ad-libitum using commercial pellet with protein content of31˗33%. The result of the canonical function analysis of truss morfometrik thetinfoil barb on 21 characteris indicated that the individual morphological characterof population of the tinfoil barb outbreed (JK and KJ) interrelated with each other.The highest sharing component value of inter population was obtained on the fish from outbreed of KJ and JK (13,3%), while the highest of intra population was obtained of K (96,7%) and the lowest of JK (86,7%). The highest survival rate (100%) was recorded on the JK population and significantly different (P>0,05) with survival rate of 90% observed in the J population.